(3TQM (B( (3cJGH (B) (3GdKeQIs - (3CHh LYaQ CMeO Hf jhSa Hf EHQGgje GdHZOGOj GdeUQj GHf GdOGjIs; (3HWdjehS GdMcje GdbdhPjs
(3ChdgG (B:s
(3COGe Gddg HbGAc ai COhe fYeI bO MVQJ CjOc Gddg HGdCeS ef ShA GdNhV ai cJGH GdKeQI GdcdeI GdChdi bGd HWdjehS Yde GdfLe efc hefgG s
(3BNQgG (B:s
(3hWdY CHh GdPDGHI hJedc eUQ hfhGMjgG hMOK HeUQ LejY eG PcQg HWdjehS ajg JeJ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3ai GdeYgO fSNI CNQi HQbe (B131(3adcs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B229 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs